Internal marketing, organizational commitment, and job performance in sport and leisure services. Issue 2 (15th October 2019) - Chiu, Weisheng; Won, Doyeon; Bae, Jung-sup
Abstract : Purpose: The purpose of this paper is to propose a conceptual model and to investigate the relationships among internal marketing, organizational commitment and job performance in sport and fitness services. Design/methodology/approach: Data were collected using a questionnaire survey from 254 employees at each of 12 municipal sport centers in Taipei City and were analyzed primarily using structural equation modeling techniques. Findings: The results indicated that internal marketing has positive effects on organizational commitment and job performance. Moreover, organizational commitment has a positive influence on job performance and plays a partial mediating role in the relationship between internal marketing and job performance. The findings identify the relationships among internal marketing, organizational commitment and job performance. Originality/value: This study proposed and tested an empirical model linking internal marketing, organizational commitment and job performance in sport and fitness services. Moreover, this study further probed into the path of influence of internal marketing strategies on job performance of employees by including their organizational commitment in the mediating process. The findings of this study have insightful implications and emphasize the important role of internal marketing in the management of customer service in sports.